HARMONY IN DIVERSITY: STUDY ON POTENTIAL HARMONIOUS MULTICULTURAL SOCIETY "PANTARA" REGIONS (PANTI-TAPUS-RAO) NORTHERN BORDER OF WEST SUMATRA - Muhiddinur Kamal (Islam Realitas: Journal of Islamic and Social Studies, 2018)
Pantara region (Panti-Tapus-Rao) is an area that lies on the border north Sumatra Indonesia consists of diverse cultures, ethnicities, races and religions. This area is a picture of a multicultural society, scattered in various corners of the village. The society of Pantara is a homogeneous society both in terms of custom and religion in Minangkabau. During the era Pagaruyung Kingdom in Minangkabau, Pantara region was given region's special autonomy status called "Lordship of Padang Nunang" located in Rao. The status of “Lordship” as shoreline areas (regions in power) is given by the special autonomous kingdom of Pagaruyung, contributing to strengthen society of "Pantara" as an honor for indigenous of Minangkabau tradition which holds the tradition of, "Tradition founded upon Islamic law, Islamic law founded upon the Qur'an" (adat basandi syara', syara' basandi Kitabullah). The massive arrival of Batak Toba and Mandailaing in the early days of independence to Pantara region(Panti-Tapus-Rao), change homogenous society into a heterogeneous society. The diversity in Pantara region covers ethnicity and culture as well as diversity in religion. Batak Toba and Mandailing society share the same patrilineal culture, but they are different in terms of religion. Batak Toba society made Protestants association or better known as HKBP while Mandailing community embraced Islam. Minangkabau people have the same religion as the Mandailing, because both are Moslem but they are different in customs. Mandailing embraced patrilineal while indigenous Minangkabau is matrilineal. On the other hand, Batak and Minang people different both in religion and culture. Batak are Christians while the Minangkabau are Muslims. The presence of Javanese people who come when it was brought by the Dutch, and the arrival of Malay people who chose to stay in the region participated Pantara enrich the diversity of Pantara region. Pantara region now has turned into a society that is heterogeneous in terms of ethnicity, religion, culture and language, they are live together in harmony, although sometimes arise, but can be mitigated and resolved quickly.There are some factors to live in harmony in diversity within the multicultural society of Pantara: 1). Understanding of religious teachings which are sublime and peaceful, 2). Values of local wisdom, 3). Recognition of newcomers, 4). And the pattern of leadership in the community